1996
DOI: 10.1001/archinte.1996.00440140083008
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Strategy After Total Hip Replacement

Abstract: After hip replacement with conventional perioperative antithrombotic prophylaxis, oral anticoagulation administered for 6 weeks is effective in preventing recurrent DVT and symptomatic pulmonary embolism, unless the bleeding risk is very high. Moreover, this strategy is less costly compared with stopping antithrombotic prophylaxis at the time of hospital discharge. Alternatively, ultrasound screening is also effective, minimizes the risks of bleeding, and has a low marginal cost-effectiveness ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although the preliminary data on LMWH are mounting, warfarin therapy is still the preferred method of postoperative prophylaxis after hospital discharge for patients who undergo THR because it has been shown to reduce the incidence of postoperative DVT and fatal pulmonary embolism. 5,14,22,[24][25][26][27] For these reasons, our approach to VTE prophylaxis consisted of a combination of elastic stockings, intermittent pneumatic compression, and adjusted subcutaneous heparin therapy during hospitalization followed by oral warfarin therapy extending to 4 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the preliminary data on LMWH are mounting, warfarin therapy is still the preferred method of postoperative prophylaxis after hospital discharge for patients who undergo THR because it has been shown to reduce the incidence of postoperative DVT and fatal pulmonary embolism. 5,14,22,[24][25][26][27] For these reasons, our approach to VTE prophylaxis consisted of a combination of elastic stockings, intermittent pneumatic compression, and adjusted subcutaneous heparin therapy during hospitalization followed by oral warfarin therapy extending to 4 weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…32 However, high resolution color duplex scanning performed by experienced personnel achieves a good sensitivity for the detection of proximal DVT in these cases and is used by several investigators. 8,23,26,33,34 VDS was used in this study because we did not consider it appropriate to perform two sets of venograms within 1 month in patients at high risk. Recent studies showed that more than 20% of venographic results were considered inadequate, indicating that the gold standard venogram has its own limitations.…”
Section: Discussionmentioning
confidence: 99%